Kebijakan Pengawasan Iklan Pangan Olahan di Indonesia - Susyanty, Andi Leny; Supardi, Sudibyo; Handayani, Rini Sasanti; J.Herman, Max; -, Raharni (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2014)
The Act of The Republic of Indonesia Number 7 of 1996 on Food mentioned that every label and or advertisement concerning food to be sold must mention information concerning the food correctly and not misleading. The government shall regulate, supervise and the measure which are needed, in order that an advertisement concerning food which is sold does not contain information which may be misleading. This cross-sectional study was conducted to Identify legislation related to food advertisement. Primary data collection by means of indepth interviews and Round Table Discussion (RTD), as well as secondary data collection concerning institusional report and monitoring documentation has been used. The data were analysed qualitatively. The findings indicate that monitoring of food advertisement only at the provincial level. Monitoring of Processed foodstuff advertisement by testimony in broadcast media, inset in the event program at television and advertising on the Internet is not optimal and it’s required cross-sectoral coordination.